(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Cardiovascular diseases (CVD) nowadays attract public concern as a result of its high level of mortality and morbidity. Aortic-arch dimension has a strong relationship with the dimension of the chest as well as the heart, age, gender and body surface area affect aortic size. Increase in aortic caliber may be a sign of aortic disease such as aortic aneurysm. Computed Tomography (CT) is widely used in the assessment of thoracic-aorta due to its high sensitivity, specificity and availability. The study aimed at establishing normal reference values for the thoracic-aortic diameter in Kaduna State Nigeria and to study the effects of age, gender, and anthropometric-indices on aortic diameter. A prospective study was conducted in the study population between April 2021 to August 2021. A total of 384 consented patients aged between 19-65 years that met the inclusion criteria were recruited using convenience sampling method. Patients with history of cardiovascular diseases that affect aortic size were excluded. The patients underwent chest CT scan and their aortic diameters were measured. Results were analyzed using SPSS version 22. The preset p-value was set at 0.05. The mean ascending-aortic-diameter, aortic-arch and descending thoracic-aorta are 36.29±5.40 mm, 31.25 ±4.99 mm, 28.79 ±4.74 mm and 32.84±4.35 mm, 28.26±4.31 mm and 25.61±4.06 mm for males and females respectively. The results of this study shows that aortic diameter of the population is in line with the findings of most of the literature reviewed. Age, weight, BMI and BSA are independent predictive factors for thoracic-aortic diameter.